2016
DOI: 10.21307/ane-2017-024
|View full text |Cite
|
Sign up to set email alerts
|

Spatial memory formation differentially affects c-Fos expression in retrosplenial areas during place avoidance training in rats

Abstract: Authors' contributions: M.M. designed the research; M.M. and M.W. performed the research, analyzed the data and wrote the paper; M.N. performed ~20% of the research.The retrosplenial cortex is involved in spatial memory function, but the contribution of its individual areas is not well known. To elucidate the involvement of retrosplenial cortical areas 29c and 30 in spatial memory, we analyzed the expression of c-Fos in these areas in the experimental group of rats that were trained in a spatial place avoidanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Fluoxetine (FLU) is an antidepressant being a selective serotonin reuptake inhibitor (SSRI) used to treat major depressive disorders (MDDs) (Holladay et al 1998). Fluoxetine has been shown to have neuroprotective properties and to improve cognitive functions -memory in particular -in both animals (Li et al 2009, Malinowska et al 2016) and humans (Gudayol-Ferré et al 2015) and, thus, may be used to treat memory disorders in alcohol addicts (Szymańska et al 2009). Memory improvement was also observed in animals exposed to ethyl alcohol (Szymańska et al 2009, Ratajczak et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoxetine (FLU) is an antidepressant being a selective serotonin reuptake inhibitor (SSRI) used to treat major depressive disorders (MDDs) (Holladay et al 1998). Fluoxetine has been shown to have neuroprotective properties and to improve cognitive functions -memory in particular -in both animals (Li et al 2009, Malinowska et al 2016) and humans (Gudayol-Ferré et al 2015) and, thus, may be used to treat memory disorders in alcohol addicts (Szymańska et al 2009). Memory improvement was also observed in animals exposed to ethyl alcohol (Szymańska et al 2009, Ratajczak et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…As already noted, the present study did not find activity differences between the deep or superficial retrosplenial layers with respect to performance. Meanwhile, previous immediate‐early gene studies of spatial memory have found retrosplenial changes across days of training (Maviel et al ., ; Malinowska et al ., ), including switches in c‐ fos expression from deep (recent memory) to more superficial (remote memory) layers (Frankland & Bontempi, ). In addition, electrophysiological analyses of retrosplenial cortex during the development of avoidance learning have highlighted lamina activity differences with respect to different stages of learning (Gabriel et al ., , ; Gabriel & Talk, ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, immediate early gene studies started to reveal the map of learning-induced plasticity within the structures responsible for spatial memory. This third approach currently allows to visualize the progression of the memory formation process [ 12 , 13 , 28 , 29 ] as well as anatomical differences within the structures involved [ 30 , 31 ]. Our study contributes to the existing body of work by correlating the immediate early genes (IEG) activation with behavioral strategy assumed by rats during the execution of a spatial task.…”
Section: Discussionmentioning
confidence: 99%